A proposed contribution model for general Islamic insurance industry. Issue 1 (20th April 2015) - Olorogun, Lukman Ayinde
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to consider a contribution model of a general Islamic insurance industry which allowed the return of underwriting profit to the Islamic insurance participants. The objective is to create a justified and equitable means of computing contribution which maximises the expected ownership right of the Islamic insurance fund. Design/methodology/approach – The accumulation of funds and claims paid were characterised in form of accumulation and decay function over a period of time. It provides necessary and sufficient conditions for their existence and uniqueness. Mathematical derivative procedures were adopted to derive the underwriting returns to be returned to the Islamic insurance participants. Lastly, this paper recommends the incorporation of underwriting returns' variable into the traditional actuarial model and provides theoretical justification for the process. Findings – Then, the derivation of underwriting returns through convolution of accumulated funds and claims paid views in the form of Laplace Transform led to a conjecture and proved. Thereafter, the proposed and adjusted model was arrived at. Originality/value – This study, to the best knowledge of the researcher, is the first attempt in the quantification of Islamic insurance industry. Thus, the model is the first attempt of creating a justified way of calculating the Islamic insurance participants' contributions.